2013
DOI: 10.1038/srep01645
|View full text |Cite
|
Sign up to set email alerts
|

The predictability of consumer visitation patterns

Abstract: We consider hundreds of thousands of individual economic transactions to ask: how predictable are consumers in their merchant visitation patterns? Our results suggest that, in the long-run, much of our seemingly elective activity is actually highly predictable. Notwithstanding a wide range of individual preferences, shoppers share regularities in how they visit merchant locations over time. Yet while aggregate behavior is largely predictable, the interleaving of shopping events introduces important stochastic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 28 publications
0
62
0
1
Order By: Relevance
“…In [19] the authors apply the Markov models to WiFi traces at Darthmouth campus and find that the best performing model is order 2 and has a median accuracy of about 65-72%. Krumme et al [20] applied Markov models on shopping locations inferred from credit card transactions, and found that models trained on the aggregate data from a large number of people perform better than individual models. Bapierre et al [21] applied a variable-order Markov chain to the Reality Mining [6] and Geolife [22] datasets.…”
Section: Related Workmentioning
confidence: 99%
“…In [19] the authors apply the Markov models to WiFi traces at Darthmouth campus and find that the best performing model is order 2 and has a median accuracy of about 65-72%. Krumme et al [20] applied Markov models on shopping locations inferred from credit card transactions, and found that models trained on the aggregate data from a large number of people perform better than individual models. Bapierre et al [21] applied a variable-order Markov chain to the Reality Mining [6] and Geolife [22] datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Yet, they exploit the temporal dimension to explain the purchasing patterns of the products at a global scale and their outcomes do not explain the customers behavior with respect to time. The temporal dimension of purchasing habits is exploited in [11] to understand how predictable are consumers in their merchant visitation patterns by using a Markov model for predicting the customer's next shop location. Note that in these works the customer behavior is generalized at global level, while our model is personal and describes the customer habits and preferences in a concise way.…”
Section: Related Workmentioning
confidence: 99%
“…Desgraciadamente los trabajos de investigación sobre el comportamiento humano basados en este tipo de registros son todavía escasos, debido a la dificultad para acceder a estos datos. Krumme et al (2013) utilizaron datos de tarjetas de crédito para predecir las pautas de comportamiento de los consumidores. Sobolevsky et al, (2014a y 2015a) partieron de datos de los registros de transacciones con tarjetas de crédito de un gran banco para determinar el atractivo de cada una de las ciudades españolas.…”
Section: Registros De Transacciones De Tarjetas Bancariasunclassified